Poverty Reduction in Awka Metropolis: The Role of Entrepreneurship Productivity - Aggreh Meshack; Marcus Garvey Orji; Nworie Gilbert Ogechukwu (Economit Journal: Scientific Journal of Accountancy, Management and Finance, 2022)
The study examined the contribution of entrepreneurship productivity towards poverty reduction using trading SMEs in Awka South as cases of reference. Specifically, the study determined the extent to which entrepreneurial education, entrepreneurial skill acquisition and entrepreneurial innovation affect poverty reduction. Descriptive survey research design was deployed in the study. Primary data were collected using a structured questionnaire administered on a sample size of ninety-nine (99). The reliability of the questionnaire was established using Cronbach alpha statistic. Hypotheses testing was conducted with the aid of Spearman Ranked Order Correlation Coefficient at 5% level of significance. The results of the analysis revealed that: entrepreneurial education significantly contributes to poverty reduction among selected SMEs in Awka South (rho = 0.589, p-value = 0.000); entrepreneurial skill acquisition significantly influences poverty reduction among selected SMEs in Awka South (rho = 0.733, p-value = 0.000); and entrepreneurial innovation significantly helps in poverty reduction in Awka South (rho = 0.591, p-value = 0.000). Among others, it was recommended that the Anambra state government should invest more in massive entrepreneurial skill acquisition in order to help the citizens to learn various aptitudes that will enable them to be self-reliant.